2001
DOI: 10.1002/poc.398
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effect on the volume of activation and volume of the Diels–Alder reaction

Abstract: Volumes of activation, ΔV≠, and reaction, ΔV, partial molar volumes, $\bar{V}$, and enthalpies of solution, ­ΔsolH, were determined for tetracyanoethylene, cyclopentadiene, 1,3‐butadiene, trans, trans‐1,4‐diphenyl‐1,3‐butadiene and their Diels–Alder adducts at 25 °C in some solvents of π‐ and n‐donor type. The values of the activation and reaction volumes were exceptionally small in the former type of solvents. Large solvent effects on ΔsolHTCNE (up to 26 kJ mol−1), $\bar{V}$TCNE, ΔV and ΔV≠ (up to 11 cm3mol−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…This means that variations in the energy of nonspecific solvation and partial molar volume are determined by different factors. This conclusion is consistent with data of [6].…”
supporting
confidence: 95%
See 1 more Smart Citation
“…This means that variations in the energy of nonspecific solvation and partial molar volume are determined by different factors. This conclusion is consistent with data of [6].…”
supporting
confidence: 95%
“…It was shown [6,10] that in the case of specific solute3sol-vent interactions the enthalpy of solvation clearly correlates with the change in the partial molar volume. However, as far as we compare the activation and reaction volumes for the Diels3Alder reactions involving the same dienophiles and different dienes (alkylbutadienes and cyclopentadiene, on the one hand, and substituted anthracenes, on the other hand), there are no specific interactions of the dienes with the solvent.…”
mentioning
confidence: 97%
“…It has been shown that the measured data are in agreement with the assumption [11,14,31] that negative values of the activation volume in the retro-Diels-Alder reactions can be caused by different possibilities of penetration of the solvent molecules into large sterically hindered branched structures in the transition states and adduct. This corresponds to the fact that solvation of the substance is determined not only by the nature of intermolecular interactions, but also the probability of their realization (steric solvation effect).…”
Section: Discussionsupporting
confidence: 75%
“…It is well known [1,4,[9][10][11] that the rate of isopolar DAR is weakly dependent (if any) on the polarity of the medium. Only a strong donor-acceptor interaction, which is observed, for example, for π -acceptor tetracyanoethylene in the medium of π -donors (alkylbenzenes), significantly reduces the activity of dienophile and its rate in the direct reaction [4,[11][12][13][14]. However the reaction rates of the adduct 11 decomposition are insensitive to the properties of the solvent [11].…”
mentioning
confidence: 93%
“…Rate constants (k -1 /s -1 ) and the enthalpies (ΔH ≠ /kJ mol -1 ), entropies (ΔS ≠ /J mol -1 K -1 ), and volumes (ΔV ≠ /cm 3 mol -1 ) of activation of the decay of adduct 1 at different temperatures (T/K) in some solvents than that in inert solvents. 11 According to the data obtained (see Table 1), the rate constants and the parame ters of activation of the decay of adduct 1 in benzene and toluene do not differ from those in other solvents. The activation enthalpies of the decay of the adduct are higher by 20-30 kJ mol -1 than the balance between the energies of bond cleavage and bond formation in this reaction (66 kJ mol -1 ), which suggests a dominant contribution from the energy of σ bond cleavage in the adduct to the formation of an activation barrier.…”
mentioning
confidence: 82%